Moderating Influence of Socio-Demographic Factors on the Relationship between Social Media Applications and Guests’ Choice of Fine Dining Restaurants - Samson Kuria Kung’u; Joseph Njoroge Muiruri; Andrew Makori; Isabella Mapelu (International Journal of Applied Sciences in Tourism and Events, 2022)
The main purpose of this research was to determine the moderating influence of social demographic factors on guests’ choice of fine dining restaurants. A mixed-method (concurrent nested) was used to do the survey. Simple random sampling technique was used to select the study units while convenient sampling technique was used o pick the respondents. Quantitative data were analyzed using SPSS version 22 to generate descriptive statistics, inferential, statistics, and regression analysis. The study established that social demographic significantly influences guests’ choice of fine dining restaurants. Also revealed, was that the composite of social demographic factors is another independent variable and not a moderating variable.  The study findings encourage Managers and owners of fine dining restaurants to include infrastructure that enables guests to use social media applications. This study contributes to the understanding of theories of consumer behavior in the perspective of fine dining restaurants. Also provided is knowledge for sharing with stakeholders and for policy developments.